The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep33226
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone in patients with rapidly progressive interstitial lung disease associated with clinically amyopathic dermatomyositis

Abstract: To evaluate the efficacy of pirfenidone in patients with rapidly progressive interstitial lung disease (RPILD) related to clinically amyopathic dermatomyositis (CADM), we conducted an open-label, prospective study with matched retrospective controls. Thirty patients diagnosed with CADM-RPILD with a disease duration <6 months at Renji Hospital South Campus from June 2014 to November 2015 were prospectively enrolled and treated with pirfenidone at a target dose of 1800 mg/d in addition to conventional treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 20 publications
2
63
0
Order By: Relevance
“…In contrast with other MSAs, 20 which are associated with infrequent pulmonary involvement, anti-MDA5 antibodies are associated with rapidly progressive forms of ILD (i.e., acute or subacute ILD), potentially leading to death. 21,22 One report suggests that pirfenidone added to corticosteroids (CSs) and/or immunosuppressive therapy may be beneficial in patients with rapidly progressive ILD associated with CADM 23 ; however, this observation warrants confirmation.…”
Section: Anti-mda5 Autoantibodies-associated Ildmentioning
confidence: 99%
“…In contrast with other MSAs, 20 which are associated with infrequent pulmonary involvement, anti-MDA5 antibodies are associated with rapidly progressive forms of ILD (i.e., acute or subacute ILD), potentially leading to death. 21,22 One report suggests that pirfenidone added to corticosteroids (CSs) and/or immunosuppressive therapy may be beneficial in patients with rapidly progressive ILD associated with CADM 23 ; however, this observation warrants confirmation.…”
Section: Anti-mda5 Autoantibodies-associated Ildmentioning
confidence: 99%
“…These two clinical trials and the long-term follow-up of the subjects showed that the most common adverse events were skin-related like rash and gastrointestinal-related containing nausea and dyspepsia [9][10][11]. Research has been conducted on the use of pirfenidone in other types of pulmonary fibrosis, such as scleroderma-associated interstitial lung disease [12][13][14] and clinically amyopathic dermatomyositis [15], and potential benefits were reported.…”
mentioning
confidence: 99%
“…ILD in DM/PM proceeds rapidly and the condition is usually severe, such as rapidly progressive ILD (RP-ILD) [11] [12]. We didn't find the reports about the correlation between miR-200c, miR-125b and ILD in DM/PM.…”
Section: Introductionmentioning
confidence: 92%